2020
DOI: 10.1038/s41598-020-77558-1
|View full text |Cite
|
Sign up to set email alerts
|

EYS is a major gene involved in retinitis pigmentosa in Japan: genetic landscapes revealed by stepwise genetic screening

Abstract: Next-generation sequencing (NGS) has greatly advanced the studies of causative genes and variants of inherited diseases. While it is sometimes challenging to determine the pathogenicity of identified variants in NGS, the American College of Medical Genetics and Genomics established the guidelines to help the interpretation. However, as to the genetic screenings for patients with retinitis pigmentosa (RP) in Japan, none of the previous studies utilized the guidelines. Considering that EYS is the major causative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…By incorporating the simplified grep program in our clinical diagnostic pipeline, we detected MEI in RP1 , which can provide a definitive molecular diagnosis that is typically missed by short-read sequencing. In our cohort with compatible phenotypes (n = 273), MEI was detected in 1.8% of patients, consistent with the frequencies reported in previous studies 24 . Numa et al suggested that tier-based approach is more efficient to detect pathogenic variants in Japanese RP as following orders: (1) Sanger sequencing of two major mutations in EYS , (2) targeted sequencing of all EYS coding exons, (3) WGS, and (4) Sanger sequencing of the Alu element in RP1 24 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By incorporating the simplified grep program in our clinical diagnostic pipeline, we detected MEI in RP1 , which can provide a definitive molecular diagnosis that is typically missed by short-read sequencing. In our cohort with compatible phenotypes (n = 273), MEI was detected in 1.8% of patients, consistent with the frequencies reported in previous studies 24 . Numa et al suggested that tier-based approach is more efficient to detect pathogenic variants in Japanese RP as following orders: (1) Sanger sequencing of two major mutations in EYS , (2) targeted sequencing of all EYS coding exons, (3) WGS, and (4) Sanger sequencing of the Alu element in RP1 24 .…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort with compatible phenotypes (n = 273), MEI was detected in 1.8% of patients, consistent with the frequencies reported in previous studies 24 . Numa et al suggested that tier-based approach is more efficient to detect pathogenic variants in Japanese RP as following orders: (1) Sanger sequencing of two major mutations in EYS , (2) targeted sequencing of all EYS coding exons, (3) WGS, and (4) Sanger sequencing of the Alu element in RP1 24 . However, our grep program detected the RP1-Alu insertion efficiently without further experiments or sequencing and yielded no false-positives.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the larger sample size identified these two mutations as additional hotspots in Chinese populations. Two Japanese hotspot mutations, c.4957_4958insA and c.8805C > A (Numa et al, 2020), were detected less frequently in the G1 cohort, indicating differences between the hotspots among patients in the Asian population.…”
Section: Discussionmentioning
confidence: 90%
“…The overall diagnostic yield in our study was similar to those of previous studies [ 13 , 14 , 15 ], but the composition ratios of frequently found causative genes were slightly different: EYS (8.2%) and USH2A (6.8%). From previous studies, EYS variants account for the largest portion of causative genes in the East Asian region, especially in Korea and Japan; EYS variants account for 20 to 30% of RP cases, and USH2A variants cause less than 10% [ 16 , 17 , 18 ]. On the other hand, USH2A variants make up 20 to 40% and EYS variants account for less than 10% of RP cases, among the total RP population in Western or European ethnicities [ 8 , 19 , 20 ] as well as Chinese or Taiwanese populations [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%